Cost-effective support for university students learning via the Web? - David Hawkridge (Association for Learning Technology, 1998)
Academics and other knowledge-owners are creating millions of Webpages that students can use. Universities are teaching more students off-campus because the costs of on-campus provision cannot be met. Offering courses via the Web seems an attractive alternative. Academics (and students) want the courses to be high quality. Yet quality is often lacking. À course outline gets approval, then aims, objectives and content change rapidly during the teaching. Students' and tutors' inputs are seldom monitored. Students join conferences only to discover that few classmates participate actively and the tutors' advice is hard to get. Web courses risk acquiring a poor reputation.